SYNTHESIS AND REACTIONS OF 2-AMINO-4 (SUBSTITUTED PHENYL)-S, 6, 7, 8·TETRABROMO·l (2H)·PHTHALAZINONE DERIVATIVES (Biological Sciences - PJSIR, 2022)
2-Amino-4 (substituted phenyl)-5, 6, 7, 8-tetrabromo-l (2H)-phthalazinones 1a-c have been prepared via the interactionof the benzoxazones 2.a-c with hydrazine hydrate in boiling pyridine. The reaction of 1 a with carbon disulphideand hydrazine hydrate in the presence of liquid ammonia gave 2-thiosemicarbazide phthalazinone derivati ve:1..Also thereaction ofl a with each ofphenylisothiocyanate, chloroacetyl chloride and u-chl oro acetanilide gave the correspondingN-PhenyJ arninocarbothiamido, ce-chlorcacetamido and N-phenyl carbonylmethylamino phthalazinones Q., 2" lLrespectively. The biological activity of some compounds has been described.